Local ecological knowledge can support improved management of small-scale fisheries in the Bay of Bengal - Ullah, Hadayet; Wahab, Md Abdul; Rahman, Md Jalilur; Al Mamun, Shaheed Nasrullah; Kumar, Uttam; Rahman, Muhammad Arifur; Souhardya, Sazeed Mehrab; Kabir, Ilias Ebne; Hussain, Monayem; Rahman, Md. Bokthier; Chishty, Sk Md Saeef Ul Hoque (Frontiers in Marine Science, 2023)
Fishers’ local ecological knowledge (LEK) can be used to reconstruct or supplement long-term trends in heavily exploited population or poorly assessed species with low biomass. We used historical memories of small-scale fishers to understand their perceptions of changes in catch trends in marine fisheries over the last 20 years. The study aimed at evaluating how fishers could provide consistent and reliable data on major fish species/groups comparable with official catch data and to explore the potential of increasing their participation in fishery management. We conducted focus group discussions (FGDs) and key informant interviews with experienced fishers and stakeholders, using a structured template related to the catch and effort data. Using FGD data, we systematically compared changes in fish catch rates and effort over time and space. Data were collected on major groups of species that had reasonable landing over time. Overall, the analysis revealed changes in catch rate, monthly landings per landing center, factors that likely influence the catch trends, and the spatial expansion of fisheries. Our study provides insight into species’ abundance over time. Fishers’ LEK shows declining catch rates for major species and groups, but monthly harvests at landing centers have increased over two decades because of increased fishing efforts. Small-scale fishers are catching more fish from deeper waters over time, indicating a geographical expansion and/or development of fisheries beyond traditionally exploited areas. Such expansions of nearshore fisheries may result from the overfishing of nearby areas. On the contrary, this could be viewed as a positive indication of the potential for growth and development of small-scale fisheries in the region, especially in the context of the blue economy. The agreement between official statistics and fishers’ data on species catch trends over time suggests that fishers have a good understanding of their fishing system. This indicates that fishers’ knowledge could be invaluable, especially in data-poor areas. LEK integration into policy and management is thus expected to facilitate the efficient management of small-scale fisheries.